2018
DOI: 10.1021/acsnano.8b04128
|View full text |Cite
|
Sign up to set email alerts
|

Gold Nanorod Photothermal Therapy Alters Cell Junctions and Actin Network in Inhibiting Cancer Cell Collective Migration

Abstract: Most cancer-related deaths come from metastasis. It was recently discovered that nanoparticles could inhibit cancer cell migration. While most researchers focus on single-cell migration, the effect of nanoparticle treatment on collective cell migration has not been explored. Collective migration occurs commonly in many types of cancer metastasis, where a group of cancer cells move together, which requires the contractility of the cytoskeleton filaments and the connection of neighboring cells by the cell juncti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
75
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(82 citation statements)
references
References 82 publications
(136 reference statements)
4
75
0
Order By: Relevance
“…In the case of metallic nanoparticles, it is possible to produce local heating at the nanoparticle-containing cells without hurting the neighboring healthy tissues, when irradiated by a laser at a wavelength near their plasmon-resonant absorption band [107]. In this regard, gold nanorods (AuNRs) have been used in plasmonic photothermal therapy (PPTT) to block EMT, leading to a significant reduction in cancer cell collective migration [52].…”
Section: Gold Nanoparticlesmentioning
confidence: 99%
“…In the case of metallic nanoparticles, it is possible to produce local heating at the nanoparticle-containing cells without hurting the neighboring healthy tissues, when irradiated by a laser at a wavelength near their plasmon-resonant absorption band [107]. In this regard, gold nanorods (AuNRs) have been used in plasmonic photothermal therapy (PPTT) to block EMT, leading to a significant reduction in cancer cell collective migration [52].…”
Section: Gold Nanoparticlesmentioning
confidence: 99%
“…Interestingly, it has been reported that constructs based on gold nanorods exhibit nearly twofold higher signal‐to‐noise ratio than constructs based on gold nanospheres . Furthermore, because gold nanorods absorb near‐infrared light, they have been widely used in the literature for photothermal therapy, making them candidates for use in theranostic platforms …”
Section: Hybridization‐based Probesmentioning
confidence: 99%
“…Near-infrared (NIR) laser-mediated photothermal therapy has attracted interest for melanoma therapy due to its deep tissue penetration and slight absorbance [12][13][14][15][16]. Photothermal therapy also has potential use for other tumors, since additional equipment such as the optic fiber may irradiate other parts of the body [17][18][19]. Among the various photothermal agents, gold nanorods (AuNRs) have been comprehensively researched due to their excellent biocompatibility and tunable surface plasmon resonance (SPR) properties for converting NIR light into local heat [20][21][22].…”
Section: Introductionmentioning
confidence: 99%